Geology and exploration of groundwater potential in hard rock using Resistivity Method (ERI) at UMK, Jeli, Kelantan. - Nadia Ramli (2021)
The location of study area is at Universiti Malaysia Kelantan (UMK), Jeli. There are two main objectives of this research, to produce an updated geological map of study area with the scale of 1:25 000. Next, to identify the potential of groundwater in hard rock using resistivity method (ERI) in order to fulfill the demands of water supply for the use in future. For geological mapping, the geomorphology, lithology and geological structure were identified. There are two major lithologic unit that can be identified in the study area. It is composed of meta-sedimentary rock which consist of phyllite from the Telong Formation and granite intrusion from Triassic Period. Mostly the study area is dominated by weathered granitic rock. A Schlumberger configuration arrays were used with 41 electrodes and 200 meters spread length through four survey lines in the study area. The data was recorded using ABEM Terrameter LS. A two-dimensional (2D) resistivity data pseudo section is produced with clear resistivity image which indicate the groundwater potential at certain depth in fractured zone of granitic bedrock.